2016
DOI: 10.1021/acs.nanolett.5b05157
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Phase Transformation in Self-Assembled InAs Nanowire Junctions on Patterned Si Substrates

Abstract: We demonstrate the growth and structural characteristics of InAs nanowire junctions evidencing a transformation of the crystalline structure. The junctions are obtained without the use of catalyst particles. Morphological investigations of the junctions reveal three structures having an L-, T-, and X-shape. The formation mechanisms of these structures have been identified. The NW junctions reveal large sections of zinc blende crystal structure free of extended defects, despite the high stacking fault density o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 47 publications
4
37
0
Order By: Relevance
“…This method requires a subsequent etching step to expose gate-tunable wire segments without metal. Nanowires have also been grown on opposite crystal facets of etched trenches 11 , 26 , which enables the formation of shadowed junctions without the need to etch the superconductor 11 . The native oxide that forms during the ex-situ processing is removed prior to the deposition of the superconductor.…”
Section: Resultsmentioning
confidence: 99%
“…This method requires a subsequent etching step to expose gate-tunable wire segments without metal. Nanowires have also been grown on opposite crystal facets of etched trenches 11 , 26 , which enables the formation of shadowed junctions without the need to etch the superconductor 11 . The native oxide that forms during the ex-situ processing is removed prior to the deposition of the superconductor.…”
Section: Resultsmentioning
confidence: 99%
“…This method requires a subsequent etching step to expose gate-tunable wire segments without metal. Nanowires have also been grown on opposite crystal facets of etched trenches [11,24], which enables the formation of shadowed junctions without the need to etch the superconductor [11].…”
Section: Shadow-wall Lithographymentioning
confidence: 99%
“…We now consider the low-temperature electrical properties of the MBE-grown InSb NCs. Previous studies of InAs [27][28][29][30] and InSb NCs [17,21,31] have confirmed transport both along and between the two merged NWs, where both ballistic transport at high fields [31] and phase-coherence [21] have been demonstrated. A main reason for using branched nanostructures is the potential to individually gate control nanowire branches, thus enabling e.g.…”
Section: Resultsmentioning
confidence: 95%